Enabling Nurse-Patient Communication With a Mobile App: Controlled Pretest-Posttest Study With Nurses and Non-English-Speaking Patients - David Silvera-Tawil; Courtney Pocock; DanaKai Bradford; Andrea Donnell; Jill Freyne; Karen Harrap; Sally Brinkmann (JMIR Publications, 2021)
BackgroundThere is growing concern regarding the implications of miscommunication in health care settings, the results of which can have serious detrimental impacts on patient safety and health outcomes. Effective communication between nurses and patients is integral in the delivery of timely, competent, and safe care. In a hospital environment where care is delivered 24 hours a day, interpreters are not always available. In 2014, we developed a communication app to support patients' interactions with allied health clinicians when interpreters are not present. In 2017, we expanded this app to meet the needs of the nursing workforce. The app contains a fixed set of phrases translated into common languages, and communication is supported by text, images, audio content, and video content. ObjectiveThis study aims to evaluate the efficacy of the communication app to support nursing staff during the provision of standard care to patients from non-English-speaking backgrounds when an interpreter is not available. MethodsThis study used a one-group pretest-posttest sequential explanatory mixed methods research design, with quantitative data analyzed using inferential statistics and qualitative data analyzed via thematic content analysis. A total of 134 observation sessions (82 pretest and 52 posttest) of everyday nurse-patient interactions and 396 app use sessions were recorded. In addition, a total of 134 surveys (82 pretest and 52 posttest) with nursing staff, 7 interviews with patients, and 3 focus groups with a total of 9 nursing staff participants were held between January and November 2017. ResultsIn the absence of the app, baseline interactions with patients from English-speaking backgrounds were rated as more successful (t80=5.69; P<.001) than interactions with patients from non-English-speaking backgrounds. When staff used the app during the live trial, interactions with patients from non-English-speaking backgrounds were rated as more successful than interactions without the app (F2,119=8.17; P<.001; η2=0.37). In addition, the level of staff frustration was rated lower when the app was used to communicate (t80=2.71; P=.008; r=0.29). Most participants indicated that the app assisted them in communicating. ConclusionsThrough the use of the app, a number of patients from non-English-speaking backgrounds experienced better provision of standard care, similar to their English-speaking peers. Thus, the app can be seen as contributing to the delivery of equitable health care.